ANALISIS KELAYAKAN OBJEK WISATA GUA LIANG BANGKAI DESA DUKUH REJO KECAMATAN MANTEWE KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Tri Sanjaya; Khairun Nisa; Asysyifa Asysyifa (Jurnal Sylva Scienteae, 2022)
This study objective to analyze the feasibility level of the Liang Bangkai Cave Tourism Obje in South Kalimantan Province, Tanah Bumbu District, Mantewe District, Dukuh Rejo Village, namely Liang Bangkai Cave.  The method used is descriptive qualitative analysis to determine the feasibility value of the Liang Bangkai Cave tourist attraction. Assessment of tourist objects and attractions includes attractions in the form of natural caves, security, conditions around the area, accessibility, area carrying capacity, availability of clean water, and visitor arrangements. The feasibility value of the Liang Bangkai Cave tourist attraction is 77.92% so that the Liang Bangkai Cave tourist attraction is feasible to be developed as a natural cave-shaped exploration tourist attractionTujuan penelitian adalah menganalisis tingkat kelayakan Objek Wisata di Provinsi Kalimantan Selatan Kabupaten Tanah Bumbu Kecamatan Mantewe desa Dukuh Rejo yaitu Gua Liang Bangkai. Metode yang digunakan yaitu analisis kualitatif deskriptif agar dapat mengetahui nilai kelayakan wisata Gua Liang Bangkai. Objek penilaian dan daya tarik wisata meliputi daya tarik berbentuk Gua Alam, keamanan, kondisi sekitar kawasan, aksesibilitas, daya dukung kawasan, ketersediaan air bersih, dan pengaturan pengunjung. Nilai kelayakan objek wisata Gua Liang Bangkai sebesar 77,92% sehingga objek wisata Gua Liang Bangkai layak untuk dikembangkan menjadi objek wisata jelajah berbentuk gua